2020
DOI: 10.3847/1538-3881/ab7b78
|View full text |Cite
|
Sign up to set email alerts
|

Into the UV: A Precise Transmission Spectrum of HAT-P-41b Using Hubble’s WFC3/UVIS G280 Grism

Abstract: The ultraviolet-visible wavelength range holds critical spectral diagnostics for the chemistry and physics at work in planetary atmospheres. To date, exoplanet time-series atmospheric characterization studies have relied on several combinations of modes on Hubble's STIS/COS instruments to access this wavelength regime. Here for the first time, we apply the Hubble WFC3/UVIS G280 grism mode to obtain exoplanet spectroscopy from 200-800 nm in a single observation. We test the G280 grism mode on the hot Jupiter HA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 47 publications
2
62
0
Order By: Relevance
“…We argue that additional transit measurements of WASP-117b with HST/UVIS and the G280 grism could yield the necessary accuracy (200-100 ppm, Wakeford et al 2020) to constrain a haze and cloud layer in WASP-117b. A low-resolution transmission spectrum in that range would reveal cloud properties due to the different scattering slopes between 0.3 and 0.5 µm for a clear atmosphere with high metallicity, a gray cloudy and hazy atmosphere with low metallicity (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We argue that additional transit measurements of WASP-117b with HST/UVIS and the G280 grism could yield the necessary accuracy (200-100 ppm, Wakeford et al 2020) to constrain a haze and cloud layer in WASP-117b. A low-resolution transmission spectrum in that range would reveal cloud properties due to the different scattering slopes between 0.3 and 0.5 µm for a clear atmosphere with high metallicity, a gray cloudy and hazy atmosphere with low metallicity (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The authors reported an accuracy of 29-33 ppm for the broadband depth between 0.3 and 0.8 µm and 200 ppm in 10 nm spectroscopic bins. Wakeford et al (2020) observed two transits of the hot Jupiter HAT-P-41b around a quiet F star with magnitude m V = 11.08. Our target WASP-117b likewise orbits a quiet F star that is even brighter than the host star of HAT-P-42b.…”
Section: Prospects For Future Investigations With the Hst And Jwstmentioning
confidence: 97%
See 1 more Smart Citation
“…Transmission spectra of a variety of exoplanets ranging from hot Jupiters to cool rocky worlds have been observed from the near-UV to the mid-infrared by ground-and space-based instruments (e.g. Charbonneau et al, 2002;Bean et al, 2010;Wood et al, 2011;Gibson et al, 2012;Deming et al, 2013;Swain et al, 2013;Crossfield et al, 2013;Knutson et al, 2014;Sing et al, 2015;de Wit et al, 2016;Wakeford, Stevenson, et al, 2017;Kreidberg, Line, Thorngren, et al, 2018;Bruno et al, 2018;Kilpatrick et al, 2018;Benneke, Wong, et al, 2019;Chachan et al, 2019;Libby-Roberts et al, 2020;Thao et al, 2020;Wakeford et al, 2020), all of which have been shown to be impacted by aerosols.…”
Section: Aerosols In Transmissionmentioning
confidence: 99%
“…The Hubble Space Telescope (HST) has proven a productive facility for characterizing the atmospheres of transiting exoplanets. Observational studies released since 2019 alone include Arcangeli et al (2019), Benneke et al (2019aBenneke et al ( , 2019b, Chachan et al (2019), dos Santos et al (2019), Mikal-Evans et al (2019, Sing et al (2019), Spake et al (2019), Guo et al (2020), Wong et al (2020), Alam et al (2020), Fu et al (2020), Wakeford et al (2020), Carter et al (2020), Bruno et al (2020), Sotzen et al (2020), Carone et al (2020), Kreidberg et al (2020), and Colón et al (2020). Transmission spectroscopy measurements, made during primary transit, allow the composition of the day-night terminator atmosphere to be probed, while at other phases in the orbit when the irradiated dayside hemisphere is visible, the planetary emission can be constrained (for overviews, see Deming & Seager 2017;Deming et al 2019).…”
Section: Introductionmentioning
confidence: 99%